Implementing Agenda 2030 in the Arab world: Contextualization, action areas and policy planning (Public Sector Economics - submission site, 2019)
This article is a critical assessment of the implementation frameworks of Agenda 2030 in the Arab region through a study of the deficiencies pertaining to the contextualization of the Agenda in the region. Seeking to identify the scope of implementation that would allow for the eventual streamlining of action towards the achievement of all of the Sustainable Development Goals (SDGs), the authors argue that the region’s political and institutional context is one of peacebuilding and resilience-building, imposing several overarching considerations pertaining to the priority intervention areas. Drawing on the findings of Ianovichina (2018), the article identifies the key levers of peacebuilding as being the reduction of real inequalities, the resumption of public and social services, and the promotion of equity and the rule of law. It then explores the policy deficiencies underlying the mobilization of these key levers. While domestic resources mobilization remains crippled by political exclusiveness and institutional inefficiency, the implementation of foreign financing frameworks intrinsically depends on that said mobilization. The authors conclude with a “roadmap” for improvements in the contextualization of Agenda 2030 by focusing on fiscal and financial reform and on the curbing of illicit financial flows on one hand, and de-escalation and institutional peacebuilding on the other.